2016
DOI: 10.1111/jnc.13890
|View full text |Cite
|
Sign up to set email alerts
|

Fabp1 gene ablation inhibits high‐fat diet‐induced increase in brain endocannabinoids

Abstract: The endocannabinoid system shifts energy balance toward storage and fat accumulation, especially in the context of diet-induced obesity. Relatively little is known about factors outside the central nervous system that may mediate the effect of high fat diet (HFD) on brain endocannabinoid levels. One candidate is the liver fatty acid binding protein (FABP1), a cytosolic protein highly prevalent in liver, but not detected in brain, which facilitates hepatic clearance of fatty acids. The impact of Fabp1 gene abla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 88 publications
1
42
0
Order By: Relevance
“…Mice were acclimated for 1 week on a defined, 10 kcal% fat control chow (#D12450B, Research Diets, New Brunswick, NJ) known to be free of phytol and phytoestrogen. Phytol and phytoestrogen were avoided because they may impact sex differences and FABP1 expression as described earlier [62]. In each group of 16 individually-housed mice, 8 mice were continued an additional 12 weeks on this same defined diet while the other 8 mice were pair-fed based upon food weight an isocaloric high fat diet (HFD, # D12451, Research Diets, New Brunswick, NJ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice were acclimated for 1 week on a defined, 10 kcal% fat control chow (#D12450B, Research Diets, New Brunswick, NJ) known to be free of phytol and phytoestrogen. Phytol and phytoestrogen were avoided because they may impact sex differences and FABP1 expression as described earlier [62]. In each group of 16 individually-housed mice, 8 mice were continued an additional 12 weeks on this same defined diet while the other 8 mice were pair-fed based upon food weight an isocaloric high fat diet (HFD, # D12451, Research Diets, New Brunswick, NJ).…”
Section: Methodsmentioning
confidence: 99%
“…However, despite the fact that NAFLD is more prevalent in women [23,24], most HFD-induced rodent models of NAFLD have focused only on males fed HFD ad libitum (rev. in [62]. Under ad libitum feeding conditions, such male rodents strongly prefer and eat more HFD as compared to normal chow (rev.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A direct comparison of Fabp2 −/− and Fabp1 −/− mice fed high fat diets also suggested that the two enterocyte proteins play different roles in intestinal and systemic metabolism [18]. Recent works indicate that Fabp1 −/− mice shows impaired endocannabinoid system both in liver and in the brain [23,24]. …”
Section: Introductionmentioning
confidence: 99%
“…The brain does not express FABP1 (Avdulov et al, ; Myers‐Payne et al, ; Owada et al, ). Nevertheless, ablation of the Fabp1 gene (LKO) in male mice dramatically increased brain AEA and 2‐AG (Martin et al, , ). Interestingly, in females, the brain AEA and 2‐AG levels are less impacted by LKO—likely due to their much lower basal level of FABP1 and potentially also due to the selective LKO‐induced reduction in brain SCP‐2 level in females (Martin et al, , b).…”
Section: Introductionmentioning
confidence: 99%